answersLogoWhite

0

What is m -6?

User Avatar

Wiki User

โˆ™ 2014-09-03 16:12:09

Best Answer

The question m-6 equals 1. You will have to find the value of he letter M.

User Avatar

Wiki User

โˆ™ 2014-09-03 16:12:09
This answer is:
๐Ÿฆƒ
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

J's study guide

1 card

What is the name of Steve on minecraft's name

โžก๏ธ
See all cards

Steel Tip Darts Out Chart

96 cards

170

169

168

167

โžก๏ธ
See all cards

Add your answer:

Earn +20 pts
Q: What is m -6?
Write your answer...
Submit
Related questions

What is the formula for m is a multiple of 6 write the next two multiples of 6 in terms of m?

m, m+6, m+12


What is the sum of m and 6?

Sun of 6 and m


M is a multiple of 6 write the next two multiples of 6 in terms of m?

m + 6 m + 12


Negative 6 plus m equals 0?

If: -6+m = 0 Then: m = 6


What is the mean average of 6 15 and m?

The average of 6, 15 and m is (6 + 15 + m) / 3 = (21 + m)/3 = 7 + m/3


Which expression is equal to 6(3m)4?

It is 72m.


What is 6 plus m equals 13?

6 + m = 16 m = 16 - 6 = 10


What animal is about 6 m high?

A Giraffe is 6 m tall and a elephant


Factorise m squared plus 7m plus 6?

(m + 6)(m + 1)


Which is big 63 cm or 6 m?

6 m is 6 meters and it is bigger.


Is 6 km or 6000 m?

1 km = 1000 m 6 km = 6*1000 = 6000 m Hence 6 km is equal to 6000 m


How much m is in 6 km?

1 km = 1000 m so 6 km = 6*1000 = 6000 m. Simple!


Can you solve m over -6 plus 6 equals 41?

m/-6 + 6 = 41 subtract 6 from each side m/-6 = 35 multiply both sides by -6 m = -210


M plus the product of 6 and n?

m+6n


What is m divided by 6 equal?

m/6 is an algebraic term


What is 15 m 4 cm plus 6 m 2 cm?

21 m 6 cm


How do you find equation for a pyramid of oranges stacked 1 2x2 3x3 4x4?

The equation for n layers is S(n) = n(n+1)(2n+1)/6It is simplest to prove it by induction.When n = 1,S(1) = 1*(1+1)(2*1+1)/6 = 1*2*3/6 = 1.Thus the formula is true for n = 1.Suppose it is true for n = m. That is, for a pyramid of m levels,S(m) = m*(m+1)*(2m+1)/6Then the (m+1)th level has (m+1)*(m+1) oranges and soS(m+1) = S(m) + (m+1)*(m+1)= m*(m+1)*(2m+1)/6 + (m+1)*(m+1)= (m+1)/6*[m*(2m+1) + 6(m+1)]= (m+1)/6*[2m^2 + m + 6m + 6]= (m+1)/6*[2m^2 + 7m + 6]= (m+1)/6*(m+2)*(2m+3)= (m+1)*(m+2)*(2m+3)/6= [(m+1)]*[(m+1)+1)]*[2*(m+1)+1]/6Thus, if the formula is true for n = m, then it is true for n = m+1.Therefore, since it is true for n =1 it is true for all positive integers.


What is the perimeter of a rectangle 7 m multiply 6 m?

42


What is the perimeter of the rectangle 7 m x 6 m?

Perimeter of rectangle: 2*(7+6) = 26 m


What is 5 over 6 minus m over 4 equals 1 over 3?

5/6 - m/4 = 1/3. First isolate the variable m, start by adding m/4 to both sides. 5/6 = 1/3 + m/4. Then subtract 1/3 from each side. 5/6 - 1/3 = m/4. Next multiply both sides by 4. 4 ( 5/6 - 1/3 ) = m. Then solve for m. 4 ( 5/6 - 2/6 ) = m. 4 ( 3/6 ) = m 4 ( 1/2 ) = m 2 = m


What is m in this equation m times Parenthesis m minus 6 parenthesis equals 91?

m(m - 6) = 91 m(m) + m(-6) = 91 m2 - 6m = 91 subtract 91 from both sides m2 - 6m - 91 = 0 since -91 = (-13)(7) and -13 + 7 = -6, then (m + 7)(m - 13) = 0 m + 7 = 0 or m - 13 = 0 m = -7 or m = 13


Simplify the variable expression by evaluating its numerical part and enter your answer below?

m - 8 + 143 - 5the answer is m+130


What expression is equivalent to 17 plus 6 plus m?

17 + 6 + m


What is the value of m plus 6?

The value is 6 more than whatever ' m ' is.


What is 5 divided by the quantity m plus 6?

11